Topology optimization applied to the core of structural engineered wood product. (February 2023) - de Vito, Artur Fernando; Vicente, William Martins; Xie, Yi Min
Abstract: Structural-engineered wood products are used in construction as a sustainable alternative to concrete and steel. The most commonly used engineered wood products are Glued-Laminated Timber (GLULAM) and Cross-Laminated Timber (CLT), which in most productions are made of layers of wood glued under pressure. In the GLULAM, the wood fiber directions are parallel stacked in layers, while in CLT, the layers have a typical rotation of 90 ° . This work develops a topology optimization method with an objective function in displacement and volume constraint applied to the core of engineered wood products such as GLULAM and CLT structures, seeking new product designs with reduced material consumption. The optimization considers the wood's orthotropic nature and the layers' stacking. Two numerical examples are performed, the first evaluating the core of a GLULAM structure with and without periodicity constraints and the second on the core of a CLT structure with periodicity constraints. The results show that the proposed procedure can be effectively applied to the core of the engineered wood products. In addition, applying periodic constraint result in optimized topologies that help the manufacturability of the new designs. Furthermore, the proposed procedure highlights the structural differences in layer importance. Highlights: This paper applies BESO method to engineering wood core structures. Orthotropic nature of the wood and stacking layout of the structure are considered. Numerical examples of CLT and GLULAM for the structures are presented.